2022
DOI: 10.31436/imjm.v21i3.1977
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Self-efficacy, Knowledge, Attitude and Practice towards Environmental Tobacco Smoke (SE-KAP-ETSQ) in the Malay language for mothers with children below 6 years old.

Abstract: Introduction: Children under 6-years old are most susceptible to environmental tobacco smoke (ETS). Mothers spend more time with their children and need to be empowered to protect their children from ETS. The study aimed to develop and validate a Malay ETS questionnaire that measures the self-efficacy, knowledge, attitude, and avoidance practice (SE-KAP-ETSQ) among mothers with children below 6 years old. Materials and Methods: The SE-KAP-ETSQ was adapted from two questionnaires; 10-item EEQ and 29-item KAP-ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The development of this was based on the framework of knowledge, attitude, practice, and self-efficacy. [17][18][19] The selfefficacy domain assesses the perceptual abilities of individual nurses in the specific field of VA management, as well as their confidence in carrying out specific tasks. The questionnaire comprised of demographic information (9 items), specific knowledge on VA (10 items), personal attitude toward VA care practices (6 items), usual practice (7 items), and self-efficacy in VA cannulation and management (6 items).…”
Section: Study Tool and Data Extractionmentioning
confidence: 99%
“…The development of this was based on the framework of knowledge, attitude, practice, and self-efficacy. [17][18][19] The selfefficacy domain assesses the perceptual abilities of individual nurses in the specific field of VA management, as well as their confidence in carrying out specific tasks. The questionnaire comprised of demographic information (9 items), specific knowledge on VA (10 items), personal attitude toward VA care practices (6 items), usual practice (7 items), and self-efficacy in VA cannulation and management (6 items).…”
Section: Study Tool and Data Extractionmentioning
confidence: 99%
“…2. Hypothesis 2 (H2): knowledge of TCM is positively associated with the adoption of TCM treatment as well as health life practices Influence of attitudes toward TCM on TCM treatment adoption and health life behaviours In recent research on attitudes toward smoking and behaviour change, mothers decided to raise their infants in smoke-free homes out of worry for their infant's health and the impacts of secondhand smoke inhalation [2]. A study in food health research [58] has shown that consumers with positive attitudes can positively influence their hygiene and cooking habits.…”
Section: The Influence Of Tcm Culture Knowledge On Tcm Attitudes Know...mentioning
confidence: 99%